Comparative Efficacy of Gingko biloba and Ashwagandha with Caroverine in the Treatment of Idiopathic Tinnitus: An Investigative Clinical Study - Srinivasan, Meenakshi; Shree. N, Raadhika (Journal of Neonatal Surgery, 2025)
Idiopathic tinnitus, a condition characterized by the perception of sound without external stimuli, significantly affects quality of life, causing distress, anxiety, and sleep disturbances. Current treatments show inconsistent efficacy due to the multifactorial nature of tinnitus, leading to interest in alternative therapies. This randomized controlled trial aimed to compare the efficacy of Gingko biloba and Ashwagandha combined with Caroverine in managing idiopathic tinnitus. Fifty patients were divided into two groups: Group 1 received Gingko biloba (60 mg/day) with Caroverine (20 mg/day), and Group 2 received Ashwagandha (300 mg twice daily) with Caroverine (20 mg/day). Outcomes were assessed using the Tinnitus Handicap Inventory (THI) at baseline, one month, three months, and six months post-treatment. Both groups demonstrated significant reductions in THI scores (p < 0.05) over six months, with improvements in tinnitus severity and its impact on daily life. While both treatments were effective, Ashwagandha offered comparable results to Gingko biloba, positioning it as a cost-effective alternative. These findings support the combined use of herbal supplements and Caroverine for managing tinnitus, providing new insights into complementary therapies for this challenging condition. Further studies are needed to explore long-term effects and psychological benefits in diverse populations